2020
DOI: 10.1177/0363546520928649
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Importance of Graft Integrity in Arthroscopic Superior Capsular Reconstruction Using a Minimally Invasively Harvested Midthigh Fascia Lata Autograft: 3-Year Clinical and Magnetic Resonance Imaging Outcomes

Abstract: Background: The clinical importance of graft type and integrity in arthroscopic superior capsular reconstruction (ASCR) remains controversial. Purpose: To assess 3-year clinical and magnetic resonance imaging (MRI) outcomes of ASCR using a minimally invasively harvested fascia lata autograft (FLA) for irreparable rotator cuff tears (IRCTs) and to determine the clinical importance of graft integrity and whether the results change from year 2 to 3. Study Design: Case series; Level of evidence, 4. Methods: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…ASCR using either the openly harvested proximal thigh FL autograft 13 , 15 or the minimally invasively harvested mid-thigh FL autograft 2 , 5 has been shown to produce good clinical outcomes, and the present study validates the biomechanical equivalence of the 2 types of FL graft constructs with regard to the stiffness and Young’s modulus. Orthopedic surgeons and patients may find the mid-thigh harvesting of the graft advantageous versus the open harvesting technique because the mid-thigh FL autograft can be minimally invasively harvested using a reproducible technique, 3 , 25 with a low donor site morbidity.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…ASCR using either the openly harvested proximal thigh FL autograft 13 , 15 or the minimally invasively harvested mid-thigh FL autograft 2 , 5 has been shown to produce good clinical outcomes, and the present study validates the biomechanical equivalence of the 2 types of FL graft constructs with regard to the stiffness and Young’s modulus. Orthopedic surgeons and patients may find the mid-thigh harvesting of the graft advantageous versus the open harvesting technique because the mid-thigh FL autograft can be minimally invasively harvested using a reproducible technique, 3 , 25 with a low donor site morbidity.…”
Section: Discussionsupporting
confidence: 73%
“…The clinical studies on ASCR using either the proximal thigh– or mid-thigh–harvested FL autograft reported good shoulder outcomes in IRCTs. 2 , 5 , 13 , 15 However, the morphological characteristics and elastic properties of the FL have been shown to be site dependent. 21 The lateral FL has been shown to be significantly thicker than other sites (0.8 ± 0.2 mm versus 0.2 – 0.3 mm in other sites), 21 and the proximal region of the lateral FL is capable of undergoing elongation that is significantly greater than that of the middle and distal regions.…”
mentioning
confidence: 99%
“…During this procedure, a concomitant tenotomy or tenodesis of the long head of the biceps (LHB) tendon may be performed, which has been shown to contribute to the relief of shoulder pain [ 18 , 19 , 20 ]. ASCR has been shown to produce excellent clinical outcomes [ 21 ]; however, graft tear rates can range from 4.2% to 75% [ 16 , 17 , 22 , 23 , 24 ]. ASCR using a human dermal allograft presents higher tear rates than ASCR using a fascia lata autograft [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASCR has been shown to produce excellent clinical outcomes [ 21 ]; however, graft tear rates can range from 4.2% to 75% [ 16 , 17 , 22 , 23 , 24 ]. ASCR using a human dermal allograft presents higher tear rates than ASCR using a fascia lata autograft [ 23 , 24 ]. Graft tears of larger dimensions have been correlated with decreased functional outcomes compared to functionality in the intact graft condition [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, other surgical groups have also reported the results of autograft SCR, often with their own modifications. 2,3,12,16 Azevedo et al, 2 for example, utilized a fascia lata autograft harvested with a minimally invasive technique. Kholinne et al 12 reported that reinforcing a fascia lata autograft SCR with polypropylene mesh yielded improved results in graft integrity and several clinical parameters.…”
mentioning
confidence: 99%